Strategi Kepemimpinan Kepala KUA dalam Meningkatkan Kinerja Pegawai di Kantor Urusan Agama (KUA) Kecamatan Semboro Kabupaten Jember - Rany Dwi Rika Sari; Rosyadi Badar (Maddah: Journal of Advanced Da'wah Management Research, 2022)
Leadership is the approach of a leader to motivate and manage all members of his group or organization to achieve the desired organizational goals and maximize employee performance. In this case, each leader has a strategy that is applied to employees to improve the performance of their employees. The focus of this research problem includes: 1. The leadership strategy of the head of KUA in improving employee performance in the religious affairs office (KUA) Semboro district, Jember Regency, 2. Supporting factors and obstacles in improving employee performance at the Office of Religious Affairs (KUA) in Semboro District, Jember Regency. While the purpose of this study is in line with the focus of the problem. The researcher uses descriptive qualitative research method, The researcher employs observation, interview, and documentation approaches to obtain data. To use triangulation to check the data's validity. The results of this study explain that the Leadership Strategy of the Head of KUA in Improving Employee Performance in KUA Semboro District, Jember Regency as follows: establish good communication and cooperation with employees, control employee performance every day, provide motivation and approach to employees, evaluate, provide training and development, and providing rewards and punishments to employees, while the supporting factors in improving employee performance at the Office of Religious Affairs Semboro District are the available office facilities and skills possessed by employees, besides that there are inhibiting factors, namely frequent technical disturbances and lack of communication between employees.